2016
DOI: 10.3349/ymj.2016.57.3.565
|View full text |Cite
|
Sign up to set email alerts
|

Visually Estimated MRI Targeted Prostate Biopsy Could Improve the Detection of Significant Prostate Cancer in Patients with a PSA Level <10 ng/mL

Abstract: PurposeTo compare prostate cancer detection rates between 12 cores transrectal ultrasound-guided prostate biopsy (TRUS-Bx) and visually estimated multiparametric magnetic resonance imaging (mp-MRI)-targeted prostate biopsy (MRI-visual-Bx) for patients with prostate specific antigen (PSA) level less than 10 ng/mL.Materials and MethodsIn total, 76 patients with PSA levels below 10 ng/mL underwent 3.0 Tesla mp-MRI and TRUS-Bx prospectively in 2014. In patients with abnormal lesions on mp-MRI, we performed additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition, the positive prostate biopsy rate per biopsy core was 46.6% and 8.4% for MRI- and TRUS-targeted biopsy respectively. This finding translates into a potentially considerable reduction of unnecessary biopsies, biopsy cores, as well as patients' harm and costs [75] .…”
Section: Application Of New Markers and Tools In Europe And Asiamentioning
confidence: 99%
“…In addition, the positive prostate biopsy rate per biopsy core was 46.6% and 8.4% for MRI- and TRUS-targeted biopsy respectively. This finding translates into a potentially considerable reduction of unnecessary biopsies, biopsy cores, as well as patients' harm and costs [75] .…”
Section: Application Of New Markers and Tools In Europe And Asiamentioning
confidence: 99%
“…For example, the study by Exterkate et al showed csPCa detection rates of 47% in MRI‐TBx vs. 32% in TRUS‐SBx 6 . Similarly, the csPCa detection rates were 32.3% vs. 29.9% between MRI‐TBx and TRUS‐SBx in the study by Rouviere et al, and 37.8% vs. 30.9% in the study by Ahdoot et al 7,8 It has been shown that MRI‐TBx and TRUS‐SBx did not statistically differ in PCa detection, but MRI‐TBx could detect more csPCa than TRUS‐SBx because nsPCa presented negative in mp‐MRI 19–21 . This could be also confirmed by this study, which showed that MRI‐TBx had a higher csPCa detection rate than TRUS‐SBx both in TZ and in PZ, but there was no statistical difference detected in PCa diagnosis between them.…”
Section: Discussionmentioning
confidence: 93%
“…Using these MRI sequences, we showed that our approach had significant efficacy to detect clinically significant prostate cancer. 8 Although we showed the efficacy of MRI in first round prostate biopsy, the cost and extended time in-bore hindered the application of this biopsy technique. Therefore, we changed the MRI protocol in our institute for patients with economic concerns.…”
Section: Discussionmentioning
confidence: 96%
“…According to several recent studies, targeted prostate biopsy using mp-MRI is efficacious in clinically significant prostate cancer detection. 5 6 7 8 Nevertheless, this biopsy technique is not popular because of its high cost. The costs of TRUS/MRI fusion Bx and bore MRI-Bx are even greater than that of the cognitive targeted prostate biopsy technique, because the former techniques require more specialized equipment.…”
Section: Introductionmentioning
confidence: 99%